Crystal structure of bis(µ2- 4-iodopyridine-2,6-dicarboxylato-κ3O:N:O′)-bis(4-iodopyridine-2,6-dicarboxylato-κ3O:N:O′)-bis(µ2-1-(4-pyridyl)piperazine-κ2N:N′)-hexa-aqua-tetra-copper(II), C46H46Cu4I4N10O22 - Lv Benlian (Zeitschrift für Kristallographie - New Crystal Structures)
C46H46Cu4I4N10O22, monoclinic, P21/c (no. 14), a = 10.6637(2) Å, b = 18.8249(6) Å, c = 14.8626(5) Å, β = 93.853(3)°, Z = 2, V = 2976.81(15) Å3, Rgt(F) = 0.0361, wRref(F2) = 0.0726, T = 291 K.